Association between injectable progestin-only contraceptives and HIV acquisition and HIV target cell frequency in the female genital tract in South African women: a prospective cohort study. Issue 4 (April 2016) - Byrne, Elizabeth H; Anahtar, Melis N; Cohen, Kathleen E; Moodley, Amber; Padavattan, Nikita; Ismail, Nasreen; Bowman, Brittany A; Olson, Gregory S; Mabhula, Amanda; Leslie, Alasdair; Ndung'u, Thumbi; Walker, Bruce D; et al.
Summary: Background: The use of injectable progestin-only contraceptives has been associated with increased risk of HIV acquisition in observational studies, but the biological mechanisms of this risk remain poorly understood. We aimed to assess the effects of progestins on HIV acquisition risk and the immune environment in the female genital tract. Methods: In this prospective cohort, we enrolled HIV-negative South African women aged 18–23 years who were not pregnant and were living in Umlazi, South Africa from the Females Rising through Education, Support, and Health (FRESH) study. We tested for HIV-1 twice per week to monitor incident infection. Every 3 months, we collected demographic and behavioural data in addition to blood and cervical samples. The study objective was to characterise host immune determinants of HIV acquisition risk, including those associated with injectable progestin-only contraceptive use. Hazard ratios (HRs) were estimated using Cox proportional hazards methods. Findings: Between Nov 19, 2012, and May 31, 2015, we characterised 432 HIV-uninfected South African women from the FRESH study. In this cohort, 152 women used injectable progestin-only contraceptives, 43 used other forms of contraception, and 222 women used no method of long-term contraception. Women using injectable progestin-only contraceptives were at substantially higher risk of acquiring HIV (12·06 per 100 person-years, 95% CI 6·41–20·63) than women using no long-term contraception (3·71 per 100 person-years, 1·36–8·07; adjusted hazard ratio [aHR] 2·93, 95% CI 1·09–7·868, p=0·0326). HIV-negative injectable progestin-only contraceptive users had 3·92 times the frequency of cervical HIV target cells (CCR5+ CD4 T cells) compared with women using no long-term contraceptive (p=0·0241). Women using no long-term contraceptive in the luteal phase of the menstrual cycle also had a 3·25 times higher frequency of cervical target cells compared with those in the follicular phase (p=0·0488), suggesting that a naturally high progestin state had similar immunological effects to injectable progestin-only contraceptives. Interpretation: Injectable progestin-only contraceptive use and high endogenous progesterone are both associated with increased frequency of activated HIV targets cells at the cervix, the site of initial HIV entry in most women, providing a possible biological mechanism underlying increased HIV acquisition in women with high progestin exposure. Funding: The Bill and Melinda Gates Foundation and the National Institute of Allergy and Infectious Diseases.